A Novel Flexible Liquid Metal Microheater with a Textured Structure - Yuqing Li; Huimin Zhang; Zi Ye; Mingyang Liu; Wei Liu; Zhenming Li; Lin Gui (Micromachines, 2023)
In this paper, we propose a novel liquid metal microheater utilizing a textured structure. This microheater effectively solves the problem of the liquid metal in the PDMS flow channel fracturing at a certain temperature and significantly increases the maximum operating temperature that can be achieved by the current liquid metal microheater. Experimental results demonstrate that this new structured microheater can achieve a maximum operating temperature exceeding 300 °C. To explain the performance improvement and the reasons behind liquid metal fracture, corresponding experiments were conducted, and explanations were provided based on the experimental results. Subsequently, we verified the mechanical flexibility of the microheater and found that it exhibits excellent tensile and bending resistance. Finally, utilizing its good mechanical flexibility, the microheater was successfully attached to the side wall of a cup, resulting in the boiling of water.